Crescimento do capim mombaça e dinâmica do nitrogênio em solo argiloso e de textura média em resposta a aplicação de dejetos suínos - Santos, Elenara Pinto dos (2005)
The technological model developed in Paraná State is mostly based at the quality of the final product. This way, it is essential the knowledge of the coffee quality potential by every coffee producer region in order to reach profit and make the culture of planting the grain in the state even stronger. The objective of this paper is to characterize the coffee produced in the region of Jesuítas, Paraná county, and identify the physical-chemical and sensory qualities associated to the production of special coffees, as well as the critical points which block the development of such quality. 46 samples were collected in Jesuítas, all from the 2002/2003 harvest, and they were physically (classification, defect counting, grain size and apparent density), chemically (caffeine content, chlorogenic acids, tannin, total sugars, proteins, lipoids, trigonelline and title holding acidity) and sensorially qualified (drink and drinking description). Later, the characteristics were correlated and portions were joint and characterized. All the coffee samples from Jesu??tas (2002/2003 harvest) presents, physically, few defects, not only in percentage values, but also in variability. Among them, only spicy, green, and broken grains were found. Significant values of big and well formed grains for the sieve number 16 or higher were found, which is an appreciated characteristic. Concerning the sensory analysis named "cup test"?, it can be assumed that the formation of the grain and the adopted practices of handing the product, on the harvest and after it, have guaranteed a drink considered Hard or Just Soft, qualities appreciated by the coffee market. The coffee can be described as full bodied and very few acid. On the chemical composition of the grains, medium to high concentration of lipoids were analyzed, as well as high concentration of proteins and normal concentration of total sugar, tannin and chlorogenic acids. Trigonelline was considered normal under Brazilian coffee standards